Characterization of Interaction between Fe‐Infiltrates and LSM Backbone in Solid Oxide Fuel Cells. Issue 17 (26th April 2018) - Yu, Yang; Ohodnicki, Paul; Abernathy, Harry; Fan, Yueying; Kalapos, Thomas; Hackett, Gregory
Abstract : In this paper, detailed materials characterization analyses on the interaction between FeO x nanoparticles infiltrated onto a La0.8 Sr0.2 MnO3 (LSM) backbone cathode in a solid oxide fuel cell (SOFC) are reported. The infiltration process leads to an increase of 3.4% in cell performance. X‐ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), transmission electron microscopy (TEM) as well as energy dispersive X‐ray spectroscopy (EDS) and electron energy loss spectroscopy (EELS) are utilized to perform a comprehensive examination of the microstructure and chemical properties at the interface of the infiltrate and backbone materials. Mn from the LSM backbone diffuses into the FeOx infiltrate and forms a Fe‐Mn‐O spinel. A small amount of Fe also diffuses into the LSM backbone, which could partially be responsible for the enhanced performance of the cell. The valence state of Mn increases from the surface of the Fe‐Mn‐O particle into bulk LSM, with the highest value being at the interface of the Fe‐Mn‐O/LSM backbone. Possible mechanisms are discussed for the change in Mn valence state within the LSM phase. Trace amounts of Mn and La are found in the YSZ phase, as a result of interdiffusion between LSM and YSZ. Abstract : In this work, detailed materials characterization analyses using SEM, XPS, TEM, EDS, and EELS on the interaction between FeOx nanoparticles infiltrated onto a La0.8 Sr0.2 MnO3 backbone cathode in a solid oxide fuel cell are reported. The infiltration leads to an increase of 3.4% in cell performance, which is accompanied by cation interdiffusion between the backbone materials and the infiltrates.